Изменение энтропии в гибкоцепных полимерах при изотермической кристаллизации - Мовсисян, Камо
The function of adding heat to flexible-chain polymers has been observed . The amount of material and the degree of overfreezing are measured for polyethylene, in which an unbalanced processes promote the formation of crystal seeds and the growth of flexible inter-crystalline spheres. A mathematical expression can be formulated which predicts the point at which entropy occurs and the material passes into a microbiophase crystalline state which then forms isothermic crystals at a predictable temperature.
Keywords: Физика